2018
DOI: 10.1097/bot.0000000000001220
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of Pediatric Orthopaedic Transfers to a Level 1 Hospital

Abstract: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…8 McKenna et al compared pediatric patients with orthopaedic injuries who presented directly to their hospital to those who were transferred from other facilities. 11 They found that transfer patients were likely to have higher injury severity scores and were likely to occur in the evening or night (though the time of actual injury was not specified). Approximately 30% of their transfers were deemed inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…8 McKenna et al compared pediatric patients with orthopaedic injuries who presented directly to their hospital to those who were transferred from other facilities. 11 They found that transfer patients were likely to have higher injury severity scores and were likely to occur in the evening or night (though the time of actual injury was not specified). Approximately 30% of their transfers were deemed inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric orthopaedic patients with government-funded health insurance experience longer periods of time before receiving definitive treatment compared with commercially-insured patients at a national level. 1 2 3 4 5 6 , 9 , 19 20 21 22 23 24 The current literature successfully identifies these issuess but has been unable to determine why the issue exists or provide solutions that generate meaningful change. Our study attempts to localize this issue based on the timeline of care.…”
Section: Discussionmentioning
confidence: 99%